URBAN INSECURITY, FRAGMENTATION AND FORTIFIED ENCLAVES IN THE FORTALEZA METROPOLITAN REGION - Freitas, Fabiano Lucas da Silva; Costa, Maria Clelia Lustosa (Mercator, 2023)
The increase in the feeling of urban insecurity has justified the self-segregation of the middle- and high-income layers of society to fortified enclaves in the Fortaleza Metropolitan Region (RMF). The main objective of this paper is to analyze the fragmentation in stretches/sectors with the highest concentration of “private condominiums” and to evaluate the impacts resulting from the expansion of fragmenting enterprises in the socio-spatial fabric. Therefore, the study indicates a change from the model of dual segregation (center-periphery) towards the pattern of socio-spatial fragmentation that has been developing, primarily, in a small area of the eastern sector (neighborhood of Lourdes), in the southeast sector and parts of the sector south and specific stretches of the municipalities of Eusébio and Aquiraz.    Keywords : Urban Insecurity, Self-segregation, Restructuring of urban space, Socio-spatial fragmentation, Typology of fortified enclaves.